Quality parameters of pink pepper seeds as sustainability indicators - Carneiro Rodrigues, Aline Nahanna; Palermo, Gilmara Pires de; Braz, Madelon; Tiago, Breier Böer (Revista de Ciencias Agrícolas, 2020)
The poor management and marketing of rose pepper (Schinus terebinthifolius Raddi) in São Pedro D’Aldeia - RJ called the local governments’ attention to adopt measures that favor the value chain, increase income, train rural producers, and launch the first Simplified Forest Management Plan. All of this, to authorize the sustainable management of this species. This study aimed to evaluate the quality parameters of pink pepper as sustainability indicators. The following was measured: the moisture content, purity, uniformity in the sieve, and the weight of one thousand seeds in samples obtained from three different batches. The germination test was only carried out for samples from lot 3. The results showed that the high moisture content of the seeds (22.99%) has a negative effect on their quality, facilitating the action of spoilage organisms. The degree of purity was satisfactory (97.1%). The seeds from lot 1 were larger and more uniform than the seeds from lots 2 and 3. Only lot 1 presented the weight of seeds compatible with that required by MAPA. The germination rate was 72%, which did not vary between seeds of different sizes. The settlement’s extractive activity is moving towards sustainability, which can be improved by incorporating good seed collection, processing and storage practices.